Acute Kidney Injury Due to Inferior Vena Cava Stenosis After Liver Transplantation: A Case Report About the Importance of Hepatic Vein Doppler Ultrasound and Clinical Assessment. Issue 1 (October 2018) - Beaubien-Souligny, William; Pépin, Marie-Noëlle; Legault, Louis; Cailhier, Jean-François; Éthier, Jean; Bouchard, Louis; Willems, Bernard; Denault, André Y.
Rationale: Acute kidney injury (AKI) is a frequent complication after liver transplantation. In some patients, prompt intervention targeted at a specific etiology is of paramount importance. Presenting concerns of the patients: A 25 years old man with advanced liver cirrhosis caused by sclerosing cholangitis and autoimmune hepatitis underwent orthotopic liver transplantation. One month after surgery, severe AKI developed in conjunction with recurrent ascites and lower extremity edema. Notable clinical findings included a persistently low urinary sodium excretion, a bland urinary sediment, and an abnormally monophasic hepatic vein waveform on Doppler ultrasound. Diagnoses: Inferior vena cava stenosis. Interventions: Angioplasty with stent installation. Outcomes: Rapid improvement of renal function after stent installation. Lessons learned: The following case illustrates the importance of integrating clinical cues, ultrasound features, and laboratory findings. The combination of AKI associated with lower extremity edema, abnormal monophasic hepatic vein flow on Doppler ultrasound, and a low urinary sodium excretion after liver transplantation should evoke the possibility of inferior vena cava stenosis as the etiologic factor.